Manajemen Lembaga Pendidikan Islam di Madrasah: Analisis Tentang Model dan Implementasinya - Irwanto, Irwanto; Susrianingsih, Susrianingsih; Habibi, Habibi; Ardat, Ardat (Sekolah Tinggi Agam Islam Sumatera Medan, 2023)
Management of Islamic educational institutions has an important role in shaping the quality of education in line with Islamic principles. The management model of Islamic educational institutions can become the essence and complexity of the management of Islamic educational institutions, illustrating how elements of professionalism, religious values, and dimensions of leadership combine to create a holistic educational environment. In this regard, this study aims to analyze the model and implementation of the management of Islamic educational institutions in madrasas. This research was conducted at MTs. Pendidikan Agama Islam. the research method used is descriptive qualitative. The results of research at MTs. Pendidikan Agama Islam namely, the management of Islamic educational institutions demands more than conventional managerial skills. In addition to competence in planning, organizing, supervising and controlling, religious aspects play a central role in decision making and carrying out administrative tasks. The concept of sacred intention is the main driving force, inspiring action with the aim of carrying out education as a religious deed that follows the teachings of Islam. The purpose of this paper is to describe the combination of managerial attitudes and Islamic leadership values ​​as an essential foundation.